Development of a quaternary ammonium poly (amidoamine) dendrimer-based drug carrier for the solubility enhancement and sustained release of furosemide - Murugan, E.; Yogaraj, V. (Frontiers in Chemistry, 2023)
Furosemide (FRSD) is a loop diuretic that has been categorized as a class IV drug according to the Biopharmaceutics Classification System (BCS). It is used in the treatment of congestive heart failure and edema. Owing to low solubility and permeability, its oral bioavailability is very poor. In this study, two types of poly (amidoamine) dendrimer-based drug carriers (generation G2 and G3) were synthesized to increase the bioavailability of FRSD through solubility enhancement and sustained release. The developed dendrimers enhanced the solubility of FRSD 58- and 109-fold, respectively, compared with pure FRSD. In vitro studies demonstrated that the maximum time taken to release 95% of the drug from G2 and G3 was 420–510 min, respectively, whereas for pure FRSD the maximum time was only 90 min. Such a delayed release is strong evidence for sustained drug release. Cytotoxicity studies using Vero and HBL 100 cell lines through an MTT assay revealed increased cell viability, indicating reduced cytotoxicity and improved bioavailability. Therefore, the present dendrimer-based drug carriers are proven to be prominent, benign, biocompatible, and efficient for poorly soluble drugs, such as FRSD. Therefore, they could be convenient choices for real-time applications of drug delivery.